The Zscan4-Tet2 Transcription Nexus Regulates Metabolic Rewiring and Enhances Proteostasis to Promote Reprogramming - Cheng, Zhou-Li; Zhang, Meng-Li; Lin, Huai-Peng; Gao, Chao; Song, Jun-Bin; Zheng, Zhihong; Li, Linpeng; Zhang, Yanan; Shen, Xiaoqi; Zhang, Hao; Huang, Zhenghui; Zhan, Wuqiang; et al. (Cell reports (Cambridge), 2020)
Evolutionarily conserved SCAN (named after SRE-ZBP, CTfin51, AW-1, and Number 18 cDNA)-domain-containing zinc finger transcription factors (ZSCAN) have been found in both mouse and human genomes. Zscan4 is transiently expressed during zygotic genome activation (ZGA) in preimplantation embryos and induced pluripotent stem cell (iPSC) reprogramming. However, little is known about the mechanism of Zscan4 underlying these processes of cell fate control. Here, we show that Zscan4f, a representative of ZSCAN proteins, is able to recruit Tet2 through its SCAN domain. The Zscan4f-Tet2 interaction promotes DNA demethylation and regulates the expression of target genes, particularly those encoding glycolytic enzymes and proteasome subunits. Zscan4f regulates metabolic rewiring, enhances proteasome function, and ultimately promotes iPSC generation. These results identify Zscan4f as an important partner of Tet2 in regulating target genes and promoting iPSC generation and suggest a possible and common mechanism shared by SCAN family transcription factors to recruit ten-eleven translocation (TET) DNA dioxygenases to regulate diverse cellular processes, including reprogramming. [Display omitted] •Zscan4f is a sequence-specific DNA-binding transcription factor•Zscan4f, a representative of ZSCAN proteins, is a functional partner for Tet2•The ZSCAN4-TET2 complex regulates metabolic rewiring and activates proteasome activity•Recruiting TET may represent a general biochemical mechanism of ZSCAN proteins Cheng et al. show that Zscan4f recruits Tet2 to target gene promoters, promotes DNA demethylation, regulates metabolic rewiring, and activates proteasome activity, indicating a mechanism of Zscan4 to control cell fate. This study also uncovers a potential and common biochemical mechanism shared by the SCAN family to recruit TET enzymes.